Application of quality function deployment to design a liquefied petroleum gas trolley - Al Amin, Mohammed Sultan; Isa, Halim (Trans Tech Publications, Switzerland, 2014)
In Malaysia, the liquefied petroleum gas (LPG) is widely used for domestic purposes. The delivery men who are in charge of delivering the LPG cylinders to the customers are exposed to the ergonomic risk factors associated with excessive force due to the heavy steel cylinders. There are devices used to assist the delivery task, however, the devices are not efficient to be used in non elevated apartments. Due to this reason, this study aims to design an LPG cylinder trolley. Quality Function Deployment was integrated to design the LPG cylinder trolley, so that it can fulfill the delivery man's requirements, thus, an effective device to assist the delivery task is produced. Based on the findings, it can be concluded that the integration of QFD is an effective solution in designing an effective LPG cylinder trolley.